Examining the use of different sample types following decomposition to estimate year of death using bomb pulse dating. (January 2022) - Johnstone-Belford, E.; Fallon, S.J.; Dipnall, J.F.; Blau, S.
Abstract: When human remains are discovered, confirming the identification of the decedent is the first part of the forensic medical investigation. In cases where the remains are skeletonised or badly decomposed, differential preservation often increases the difficulty of this task. Bomb pulse dating, which directly compares levels of 14 C within human tissues to atmospheric levels, can provide an estimate of the year of death, which may assist in the identification process. This study measured the 14 C content in samples of hair, nail and puparia collected from donors at the Australian Facility for Taphonomic Experimental Research (AFTER). The radiocarbon results demonstrated that the nail samples provided the most accurate year of death estimation, with 91% correctly predicting YOD, closely followed by hair, with a 79% correct prediction rate, with both hair and nails having a lag time of 0–1 years. This is consistent with the time taken for atmospheric CO 2 to enter the food chain, and be taken in by humans. Puparia was found to have the highest levels of 14 C, and was the least consistent with the actual YOD (46% correct). However, predicted YOD ranges were still within 4 years of the actual YOD. Based on the results of this study, hair, nail and puparia should be considered as useful samples to obtain accurate estimates for YOD using bomb pulse dating. Highlights: Year of death can be estimated by analysing hair and nail using bomb pulse dating. Nails contain 14C levels most consistent with the year of death. Puparia can be used to estimate year of death within 4 years.